Effects of Space Weathering and Porosity on the Far‐UV Reflectance of Amundsen Crater. Issue 3 (18th March 2019) - Byron, B. D.; Retherford, K. D.; Greathouse, T. K.; Mandt, K. E.; Hendrix, A. R.; Poston, M. J.; Liu, Y.; Cahill, J. T.; Mazarico, E.
Abstract: The lunar South Pole crater Amundsen is a prime location to study the effects of space weathering in the far ultraviolet. Amundsen's equator‐facing terrace walls are highly illuminated while the northern side of the crater has permanently shaded regions (PSRs). Using data from the Lunar Reconnaissance Orbiter Lyman Alpha Mapping Project, we investigate signatures of space weathering in different regions of Amundsen. We find that regions of the surface that receive large amounts of solar illumination and solar wind flux (e.g., the southern terrace walls) display high Lyman‐α albedos and blue spectral slopes in the 175–190‐nm region, indicative of increased regolith maturity due to solar wind weathering and thermal cycling. Amundsen's PSRs, however, receive no direct solar illumination and very little solar wind flux and have a lower albedo across Lyman Alpha Mapping Project's entire band pass (57–197 nm) than illuminated regions of the crater. We conclude that the low PSR albedos correspond to high regolith porosity in the PSRs. These PSRs are extremely cold regions with very minor thermal cycling. Thermal cycling might be a process that reduces porosity in regions of the crater exposed to a wide range of temperatures, thus increasing their albedos across the entire wavelength range. However, our analysis of the present data set was unable to uniquely identify its role. The low albedos in the PSRs may also result from extreme charging effects inside the PSRs, causing lofting and redeposition of dust, as well as dielectric breakdown, which would act to increase regolith porosity. Plain Language Summary: Space weathering on the Moon is caused by the interaction of solar wind particles and micrometeoroids with the surface. The effects of these interactions can be investigated by analyzing the reflectance of the surface using data from the Lyman Alpha Mapping Project, an instrument onboard the Lunar Reconnaissance Orbiter. In this study, we analyzed one particular crater (Amundsen) near the lunar South Pole because it contains regions of high and low amounts of space weathering in close proximities. We found that regions of the crater that receive large amounts of sunlight and solar wind flux display signatures of space weathering, while regions that receive no sunlight and very little solar wind flux do not. We also found that the regions of the crater that receive no sunlight have high porosity in the upper layer of the soil, and presented a number of possible explanations for this finding. Key Points: Highly illuminated regions of Amundsen crater display signatures of space weathering in the far‐UV Amundsen's permanently shaded regions have low albedos across the full LAMP band pass, consistent with high regolith porosity Differences in porosity between illuminated and shaded regions may be a result of thermal cycling, dielectric breakdown, and/or dust lofting